Neuroprotective effects of resveratrol in an MPTP mouse model of Parkinson's-like disease: Possible role of SOCS-1 in reducing pro-inflammatory responses. Issue 3 (April 2014) - Lofrumento, Dario D; Nicolardi, Giuseppe; Cianciulli, Antonia; Nuccio, Francesco De; Pesa, Velia La; Carofiglio, Vito; Dragone, Teresa; Calvello, Rosa; Panaro, Maria A
In the present study we used a 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-induced Parkinson's disease (PD) mouse model to analyze resveratrol neuroprotective effects. The MPTP-induced PD model is characterized by chronic inflammation, oxidative stress and loss of the dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc). We observed that resveratrol treatment significantly reduced glial activation, decreasing the levels of IL-1β, IL-6 and TNF-α, as well as their respective receptors in the SNpc of MPTP-treated mice, as demonstrated by Western blotting, RT-PCR and quantitative PCR analysis. This reduction is related to possible neuroprotection as we also observed that resveratrol administration limited the decline of tyrosine hydroxylase-immunoreactivity induced in the striatum and SNpc by MPTP injection. Consistent with these data, resveratrol treatment up-regulated the expression of the suppressor of cytokine signaling-1 (SOCS-1), supporting the hypothesis that resveratrol protects DA neurons of the SNpc against MPTP-induced cell loss by regulating inflammatory reactions, possibly through SOCS-1 induction.